A bundle to prevent postinduction hypotension in high-risk noncardiac surgery patients: the ZERO-HYPOTENSION single-arm interventional proof-of-concept study - Kristen K. Thomsen; Alina Kröker; Linda Krause; Karim Kouz; Christian Zöllner; Daniel I. Sessler; Bernd Saugel; Moritz Flick (BJA Open)
Background: Postinduction hypotension is common and associated with organ injury but might be largely preventable by careful anaesthetic management. We thus aimed to quantify the severity and duration of postinduction hypotension in high-risk noncardiac surgery patients treated with a hypotension prevention bundle. Methods: In this prospective single-arm interventional proof-of-concept study, 107 high-risk noncardiac surgery patients were treated with a hypotension prevention bundle. The bundle included continuous intra-arterial blood pressure monitoring, a hypotension alarm set at a mean arterial pressure (MAP) of 75 mm Hg, careful administration of anaesthetic drugs, and continuous administration of norepinephrine when MAP decreased below 75 mm Hg. The primary endpoint, AUC65, was derived from a plot of MAP over time for the first 15 min after induction of general anaesthesia as the area of the plot under a MAP of 65 mm Hg . Results: Of 107 patients, 55 (51%) had at least one MAP reading <65 mm Hg, but only 16/107 patients (15%) had a MAP <65 mm Hg for at least one continuous minute. Patients had a MAP <65 mm Hg for a median (25% percentile, 75% percentile; minimum–maximum) of 0.2 min (0.0, 0.8; 0.0–5.2 min). The median AUC65 was 0.1 mm Hg . min (0.0, 4.1; 0.0–40.6 mm Hg min). Conclusions: We observed minimal postinduction hypotension in high-risk noncardiac surgery patients treated with a hypotension prevention bundle. However, randomised trials are needed to confirm that using the hypotension prevention bundle helps reduce postinduction hypotension.